Design sensitivity analysis of three-storey reinforced concrete moment-resisting frame structures using performance-based wind engineering - Olivas, Ana Claudinne E.
In this paper, the sensitivity of the performance of model structures to modifications made on different design variables are derived. The design variables considered were the roof pitch and building plan dimensions, while the damage indicators considered were roof cover and window failure. The methodology implemented involves three major steps: hazard characterization, performance assessment of structures in the building database, and sensitivity analysis of the performance to the changes made in the design variable. Results show that, for modifications made to roof pitch, sensitivity indices obtained range from 0.07 to 1. For modifications made to plan dimensions, sensitivity indices ranged from 0.02 to 1. Considering vulnerability, modifications made to roof pitch resulted in sensitivity indices ranging from 0.3 to 0.8, while modifications to plan dimensions resulted a range of 0.3 to 0.73. However, as wind speed increases the sensitivity of performance to modifications in these variables decreases, with sensitivity index plots of both variables approaching each other.